Influence of photoperiod and running wheel access on the entrainment of split circadian rhythms in hamsters - Elliott Jeffrey A; Evans Jennifer A; Vakili Martin M; Rosenthal Sheila L; Gorman Michael R (BMC Neuroscience, 2005)
Abstract Background In the laboratory, behavioral and physiological states of nocturnal rodents alternate, with a period near 24 h, between those appropriate for the night (e.g., elevated wheel-running activity and high melatonin secretion) and for the day (e.g., rest and low melatonin secretion). Under appropriate 24 h light:dark:light:dark conditions, however, rodents may be readily induced to express bimodal rest/activity cycles that reflect a global temporal reorganization of the central neural pacemaker in the hypothalamus. We examine here how the relative length of the light and dark phases of the environmental cycle influences this rhythm splitting and the necessity of a running wheel for expression of this entrainment condition. Results Rhythm splitting was observed in wheel-running and general locomotion of Siberian and Syrian hamsters. The latter also manifest split rhythms in body temperature. Access to a running wheel was necessary neither for the induction nor maintenance of this entrainment pattern. While rhythms were only transiently split in many animals with two 5 h nights, the incidence of splitting was greater with twice daily nights of shorter duration. Removal of running wheels altered the body temperature rhythm but did not eliminate its clear bimodality. Conclusion The expression of entrained, split circadian rhythms exhibits no strict dependence on access to a running wheel, but can be facilitated by manipulation of ambient lighting conditions. These circadian entrainment patterns may be of therapeutic value to human shift-workers and others facing chronobiological challenges.